How Fiscal Policies Affect Credit Rates: Probit Analysis of Three Main Credit Rating Agencies’ Sovereign Credit Notes - Eda Balikçioğlu; Hakki Hakan Yilmaz (Transylvanian Review of Administrative Sciences, 2019)
The aim of this study is to identify the relationship between fiscal policy and sovereign credit ratings within a comparative framework for the post-2000 period. In this study, indicators affecting credit notes of three rating agencies through domestic savings, growth, inflation, unemployment, current account balance and public revenues, public expenditures, primary deficits, budget deficits and public debt data for selected countries for the period between 2001 and 2016 are evaluated by using probit analysis under four scenarios. The study reveals that growth, unemployment, savings, current account deficit and public debt have come to the forefront in the realizations and far estimates, while the main indicators in the public sector, namely the impact of expenditure, deficit, primary balance and debt on rating decisions, are more dominant in the near estimates. These results show that the factors that are differentiating the credit rating evaluation period are the indicators of public finance. It seems that models used by the credit institutions are more likely to show short-term outcomes in the sense of public finance parameters mainly reflecting the macroeconomic responsibility level of the ruling governments.